Hubungan Antara Kepribadian, Self-efficacy, dan Dukungan Teman dengan Perilaku Caring Mahasiswa Profesi Ners - Nursalam Nursalam; Afita Nur Dwiyanti; Candra Panji Asmoro (FORIKES, 2021)
Nurse students must have caring behavior when providing services, but they have difficulty understanding the meaning and practice of caring behavior. The purpose of this study was to determine the relationship between the big five personality, self-efficacy, and social support from friends with the caring behavior of the nurse profession students. The design of this study was cross-sectional. The study population was all students of the nurse profession, Faculty of Nursing, Airlangga University in 2020. The sample size was 104 students who were selected using simple random sampling. Data were collected using a questionnaire that has been tested for validity and reliability, then analyzed using logistic regression test. The results showed a relationship between caring behavior and big five personality factors, especially extraversion personality p = 0.046, agreeableness p = 0.014, conscientiousness p = 0.005, self-efficacy p = 0.035, and social support from friends p = 0.003. Openness to experience (p = 0.368) and neuroticism (p = 0.373) were not related to caring behavior. It is recommended that educators provide more examples (role models) of how to behave in proper caring, so that students of the nurse profession can improve their caring behavior. Keywords: caring; social support; personality; self-efficacy ABSTRAK Mahasiswa profesi ners harus memiliki perilaku caring ketika memberikan pelayanan, namun mereka mengalami kesulitan untuk memahami makna dan praktik dari perilaku caring. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kepribadian big five, self-efficacy, dan dukungan sosial teman dengan perilaku caring mahasiswa profesi ners. Desain penelitian ini adalah cross-sectional. Populasi penelitian adalah seluruh mahasiswa profesi ners, Fakultas Keperawatan, Universitas Airlangga tahun 2020. Besar sampel adalah 104 mahasiswa yang dipilih menggunakan simple random sampling. Data dikumpulkan menggunakan kuesioner yang telah di uji validitas dan reliabilitas, lalu dianalisis menggunakan uji regresi logistik. Hasil penelitian menunjukkan adanya hubungan antara perilaku caring dengan faktor kepribadian big five, khususnya kepribadian extraversion p=0.046, agreeableness p=0,014, conscientiousness p=0,005, self-efficacy p=0,035, dan dukungan sosial teman p=0,003. Kepribadian openness to experience (p=0.368) dan neuroticism (p=0.373) tidak berhubungan dengan perilaku caring. Disarankan agar pendidik lebih memberikan contoh (role model) bagaimana sikap berperilaku caring yang tepat, sehingga mahasiswa profesi ners dapat meningkatkan perilaku caring mereka. Kata kunci: caring; dukungan sosial; kepribadian; self-efficacy